Plasma DNA methylation: a potential biomarker for stratification of liver fibrosis in non-alcoholic fatty liver disease. Issue 7 (21st March 2016) - Hardy, Timothy; Zeybel, Mujdat; Day, Christopher P; Dipper, Christian; Masson, Steven; McPherson, Stuart; Henderson, Elsbeth; Tiniakos, Dina; White, Steve; French, Jeremy; Mann, Derek A; Anstee, Quentin M; et al.
Abstract : Objective: Liver biopsy is currently the most reliable way of evaluating liver fibrosis in patients with non-alcoholic fatty liver disease (NAFLD). Its inherent risks limit its widespread use. Differential liver DNA methylation of peroxisome proliferator-activated receptor gamma (PPARγ) gene promoter has recently been shown to stratify patients in terms of fibrosis severity but requires access to liver tissue. The aim of this study was to assess whether DNA methylation of circulating DNA could be detected in human plasma and potentially used to stratify liver fibrosis severity in patients with NAFLD. Design: Patients with biopsy-proven NAFLD and age-matched controls were recruited from the liver and gastroenterology clinics at the Newcastle upon Tyne Hospitals NHS Foundation Trust. Plasma cell-free circulating DNA methylation of PPARγ was quantitatively assessed by pyrosequencing. Liver DNA methylation was quantitatively assessed by pyrosequencing NAFLD explant tissue, subjected to laser capture microdissection (LCM). Patients with alcoholic liver disease (ALD) were also subjected to plasma DNA and LCM pyrosequencing. Results: 26 patients with biopsy-proven NAFLD were included. Quantitative plasma DNA methylation of PPARγ stratified patients into mild (Kleiner 1–2) and severe (Kleiner 3–4) fibrosis (CpG1: 63% vs 86%, p<0.05; CpG2: 51% vs 65% p>0.05). Hypermethylation at the PPARγ promoter of plasma DNA correlated with changes in hepatocellular rather than myofibroblast DNA methylation. Similar results were demonstrated in patients with ALD cirrhosis. Conclusions: Differential DNA methylation at the PPARγ promoter can be detected within the pool of cell-free DNA of human plasma. With further validation, plasma DNA methylation of PPARγ could potentially be used to non-invasively stratify liver fibrosis severity in patients with NAFLD. Plasma DNA methylation signatures reflect the molecular pathology associated with fibrotic liver disease.